Sinophone, Chinese and, PRC Internet: Chinese Overseas in Australia and the PRC Internet - Leong, Susan (Brill, 2016)
Recently, while there have been some who advocate the notion of a Sinophone internet, approximately coterminous with a Chinese-literate user base (Sullivan & Chen 2015), others have argued the internet in China should be known as the Chinese internet (Yang 2015: 1). This paper extends from the call to specificity to ask how the suggestion of the Chinese internet might manifest itself and what it might mean for the Chinese overseas. This is specifically in light of the multiplicity and heterogeneity of the Chinese diaspora in Australia, where many individuals of Chinese ancestry may or may not speak, read, or understand Putonghua (i.e. Mandarin). Rather than the Chinese internet, this paper proposes that we think of the People’s Republic of China (PRC) internet as one component of the multiple internets. Recently, while there have been some who advocate the notion of a Sinophone internet, approximately coterminous with a Chinese-literate user base (Sullivan & Chen 2015), others have argued the internet in China should be known as the Chinese internet (Yang 2015: 1). This paper extends from the call to specificity to ask how the suggestion of the Chinese internet might manifest itself and what it might mean for the Chinese overseas. This is specifically in light of the multiplicity and heterogeneity of the Chinese diaspora in Australia, where many individuals of Chinese ancestry may or may not speak, read, or understand Putonghua (i.e. Mandarin). Rather than the Chinese internet, this paper proposes that we think of the People’s Republic of China (PRC) internet as one component of the multiple internets.